Responsible AI Governance: Frameworks for Ethical AI Use (Journal of responsible AI & ethics, 2026)
The rapid development of Artificial Intelligence (AI) has raised significant questions about its ethical implications, particularly as AI systems are increasingly deployed in sensitive sectors such as healthcare, criminal justice, finance, and autonomous vehicles. Responsible AI governance is crucial for ensuring that AI technologies are developed and used in ways that align with ethical principles, protect human rights, and mitigate risks. This paper explores the frameworks for ethical AI use and the governance structures necessary to ensure accountability, transparency, fairness, and inclusivity in AI systems. By reviewing existing AI governance models, examining their strengths and weaknesses, and considering their applicability in real-world contexts, the paper highlights the critical elements of a responsible AI governance framework. Drawing from case studies of organizations and nations that have successfully implemented ethical AI practices, the paper provides actionable recommendations for fostering responsible AI governance. The study concludes with suggestions for enhancing AI regulations, promoting public trust, and developing international standards for ethical AI use.